Perancangan Telemetri Aktivitas Gunung Berapi Menggunakan Sensor Seismik 3C Dengan Gelombang Wifi 2.4GHz - Alwan, Chotib; Zacoeb, Achfas; H. Santjojo, D. J Djoko; R. Santoso, Didik (Rekayasa Sipil, 2017)
Remote monitoring using high-frequency Wifi telemetry communications media is a solution that enables to benefits from data transfer speed, remote communication, data security system and uses less energy. This study aims to establish a telemetry communication system of integrated sensor networks for the volcanic geographic area with some advantages such as the physical parameters of a volcano conditions accurately in real-time and online, the higher transmission speed, easily duplicated, and the flexibility for additional high sensors as a part of the decision making to determine the volcano status. Wifi telemetry 2.4GHz offers a high data transfer speed, the current supported equipment or modules have been reached a speed of 100Mbps. Range coverageâs performed on this test reached a maximum distance of 2 km line of sight, the data in the form of sensor data and moving images. The visual data expected is not in fully real-time, because there are 5 seconds delays from the production time. To use a shorter delay in order to the image goes faster, the main processor of raspberry experienced some over heat, and then it is not suitable for a long-term continuous use.Â